2008
DOI: 10.1124/mol.108.049205
|View full text |Cite
|
Sign up to set email alerts
|

The Cannabinoid CB1 Receptor Antagonist Rimonabant Stimulates 2-Deoxyglucose Uptake in Skeletal Muscle Cells by Regulating the Expression of Phosphatidylinositol-3-kinase

Abstract: The endocannabinoid system regulates food intake, energy, and glucose metabolism at both central and peripheral levels. We have investigated the mechanism by which it may control glucose uptake in skeletal muscle cells. Detectable levels of the cannabinoid receptor type 1 (CB1) were revealed in L6 cells. Exposure of differentiated L6 myotubes to the CB1 antagonist rimonabant (SR141716) selectively increased 2-deoxyglucose uptake (2-DG) in a time-and dose-dependent manner. A similar effect was induced by geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 47 publications
10
83
1
2
Order By: Relevance
“…Our finding that acute agonism of CB1R impaired insulin-stimulated Akt phosphorylation is in agreement with several in vitro studies that have shown rapid effects of CB1R modulation on insulin signalling. For example, Esposito et al demonstrated that SR141716 stimulated 2-DG uptake in L6 cells through phosphatidylinositol 3-kinase and downstream proteins, including Akt, an effect observed as early as 30 min post treatment [46]. In human skeletal muscle cells, treatment with the CB1R agonist anandamide for 1 h increased ERK1/ 2 and p38 mitogen-activated protein kinase, and impaired insulin-stimulated phosphorylation of Akt (Ser473), but not of Akt (Thr308) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that acute agonism of CB1R impaired insulin-stimulated Akt phosphorylation is in agreement with several in vitro studies that have shown rapid effects of CB1R modulation on insulin signalling. For example, Esposito et al demonstrated that SR141716 stimulated 2-DG uptake in L6 cells through phosphatidylinositol 3-kinase and downstream proteins, including Akt, an effect observed as early as 30 min post treatment [46]. In human skeletal muscle cells, treatment with the CB1R agonist anandamide for 1 h increased ERK1/ 2 and p38 mitogen-activated protein kinase, and impaired insulin-stimulated phosphorylation of Akt (Ser473), but not of Akt (Thr308) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Akt activation by CB1 receptor antagonist rimonabant has been reported in L6 skeletal muscle cells and in mouse primary myocytes [4] . In these cells, rimonabant increased 2-deoxyglucose uptake, which was blunted by co-incubation with the PI3K inhibitor LY294002.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CB1 blockade in adipose tissue induces decreased abdominal fat, increased adiponectin and HDL, decreased triglycerides (TG), low-density lipoprotein (LDL), C-reactive protein (CRP), decreased insulin resistance and glycosylated hemoglobin [1] . Rimonabant also stimulates 2-deoxyglucose uptake in skeletal muscle cells [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Muscle cells produce endocannabinoids and express cannabinoid receptors and metabolic enzymes (165, 234,249,483). In the skeletal muscle, CB1 activation by endocannabinoids plays a role in the development of insulin resistance, possibly by enhancing IRS-1 phosphorylation and ERK activation (234,483).…”
Section: Skeletal Musclementioning
confidence: 99%